Analisis Pemasaran Pada Usaha Mikro Kecil Menengah Kerajinan Kaligrafi Kulit Kambing di Kecamatan Sukoharjo Kabupaten Sukoharjo - Riezka Aditya Perdana; Shanti Emawati; Ayu Intan Sari (Universitas Sebelas Maret (UNS), 2015)
This research aimed to find out the marketing channel pattern, price, marketing cost,marketing margin, profit and marketing efficiency of goat calligraphy handicraft marketing inSukoharjo Sub District of Sukoharjo Regency. The sample used is 30 goat leather calligraphyhandicraft producers, 3 intermediaries and 6 retailers. This study was conducted using survey; themethods of analyzing data used were cost analysis, margin, profit, and marketing efficiency analyses.The result of research showed that there were 3 marketing channels for goat leather calligraphyhandicraft: First Channel: Producer to Consumer, Second Channel: Producer to Retailer toConsumer, and Third Channel: Producer to Intermediary to Retailer to Consumer. The highestmarketing cost in the third channel was IDR 921.00 and the lowest one was IDR 0.00. The highestmarketing margin occurred in the third channel of IDR 10,000.00 and the lowest one in the firstchannel of IDR 0.00. The highest marketing profit occurred in the third channel of IDR 9,079.00,while the lowest one was IDR 0,00 occurring in the first channel. The Highest marketing efficiencyoccurred in the first channel was 100%, followed by second channel 89%, third channel 73%. Thethree marketing channels had been efficient because the efficiency value obtained was >50%. Themost efficient marketing was the first channel but the most widely used by producer was the thirdchannel.